Visual discrimination learning for english words for dyslexic children using web based virtual reality (VR) system - Lim, Jannicia Yen Yen (Universiti Malaysia Sarawak (UNIMAS), 2009)
This project aims to design and develop a Web Based Virtual Reality learning system using desktop virtual reality (VR). This learning system was designed for dyslexic children to learn visual discrimination for English words. Generally, the learning system incorporates dyslexic learning requirement, design guidelines for system development and user feedback to produce the effective system for target users. Users' feedbacks of using the system were obtained. Based on the feedback results, some recommendations of future works are suggested to enhance the system.